2022
DOI: 10.1155/2022/6281892
|View full text |Cite
|
Sign up to set email alerts
|

Magnoliae flos Downregulated Lipopolysaccharide-Induced Inflammatory Responses via NF-κB/ERK-JNK MAPK/STAT3 Pathways

Abstract: Background. Magnoliae flos is the dried flower bud of Magnolia biondii and related plants. It has been used as a medicinal herb for the treatment of rhinitis, sinusitis, and sinus headaches. Nevertheless, the effects of Magnoliae flos in microbial infection or sepsis remain unclear. In this study, we investigated the anti-inflammatory effects of Magnoliae flos water extract (MF) in lipopolysaccharide- (LPS-) induced septic mice and LPS-stimulated RAW264.7 macrophages. Results. We found that MF reduced the mort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…In traditional medicine, MF has been used to treat allergic rhinitis, sinusitis, nasal congestion, headaches, and toothache and is prescribed as Shinyicheongpye-tang (辛夷淸肺湯) or Shinyisan (辛夷散) [ 21 , 22 ]. Several studies have reported that MF has anti-allergic, anti-inflammatory, antibacterial, antioxidant, and neuroprotective activities and inhibitory effects on ovariectomy-induced osteoporosis [ 23 , 24 , 25 , 26 , 27 ]. Its active compounds include neolignans, magnolin, magnolol, eudesmin, vanillic acid, and fargesin, and these are reported to have anti-inflammatory, antibacterial, anti-allergic, and anti-obesity effects [ 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…In traditional medicine, MF has been used to treat allergic rhinitis, sinusitis, nasal congestion, headaches, and toothache and is prescribed as Shinyicheongpye-tang (辛夷淸肺湯) or Shinyisan (辛夷散) [ 21 , 22 ]. Several studies have reported that MF has anti-allergic, anti-inflammatory, antibacterial, antioxidant, and neuroprotective activities and inhibitory effects on ovariectomy-induced osteoporosis [ 23 , 24 , 25 , 26 , 27 ]. Its active compounds include neolignans, magnolin, magnolol, eudesmin, vanillic acid, and fargesin, and these are reported to have anti-inflammatory, antibacterial, anti-allergic, and anti-obesity effects [ 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%